PERPETUATION, TRANSMISSION AND MANAGEMENT OF CURVULARIA LEAF SPOT OF GLADIOLUS1 - HANUMAN SINGH; P. J. SINGH; JITENDRA KUMAR (The Bioscan, 2014)
Systemic and non-systemic fungicides evaluated in pots as well as in field. In field, the minimum disease severity was recorded in Antracol, Score and Tilt (1.33), followed by Dithane M-45, Kavach and Topas (1.67). Moderate disease severity found in Cuman-L, Blitox and Bavistin sprayed plant (2.33). Yield data showed that the highest number of corms/plot, highest weight of the corms/plot and cormels/plot recorded in Score (58.00) (1.40 kg) (577.67) respectively. In the present studies in both the field and pot experiments Score found to be the most promising fungicide against Curvularia trifoliii f. sp. gladioli. The other promising fungicides were Tilt, Kavach, Antracol and Dithane M-45. Bavistin was the least effective fungicide. The fungus C. trifolii f. sp. gladioli did not survive in pots containing sterilized soil during the off-season. Colonies of fungus C. trifolii f. sp. gladioli could not observed from the artificially inoculated soil by dilution plate method.